In situ analysis of interleukin-6 expression at different sites of zygapophyseal joints from patients with ankylosing spondylitis in comparison to controls. (July 2015) - Bleil, J; Maier, R; Syrbe, U; Sieper, J; Appel, H
<x xml:space="preserve">Abstract</x> Objectives: Analysis of interleukin (IL)-6 serum levels in patients with ankylosing spondylitis (AS) has indicated that IL-6 might be a pro-inflammatory cytokine involved in AS. However, two placebo-controlled trials with monoclonal antibodies directed against the IL-6 receptor have failed to demonstrate the efficacy of the monoclonal humanized anti-human IL-6 receptor antibody over placebo for the treatment of symptoms of AS. In this study we conducted an in situ analysis of IL-6 expression at different sites of inflammation in zygapophyseal joints of patients with AS in comparison to osteoarthritis autopsy controls (CO). Method: Our immunohistochemical analysis involved 14 patients with AS, 12 autopsy controls (CO), and 11 patients with osteoarthritis (OA). Immunohistochemistry was performed to detect IL-6+ cells at five different sites: within subchondral bone marrow, fibrous tissue replacing subchondral bone marrow, hyaline cartilage, and the subchondral bone plate, and at entheseal sites. Results: Apart from changes in subchondral bone marrow, no significant differences were observed at the sites analysed when comparing AS patients and controls. A significantly lower frequency of IL-6+ cells was evident in AS patients compared to controls (p = 0.0043). In addition, AS patients tended to have even lower percentages of IL-6+ cells than controls at subchondral bone plates and entheseal sites. A significantly lower number of IL-6 expressing cells was also seen within the fibrous tissue of AS compared to OA patients (p = 0.0237). Conclusions: This in situ analysis confirms that IL-6 is not a key player in the pathogenesis of inflammatory processes in spondyloarthritides (SpA). The relevance of pro-inflammatory agents in axial SpA might be studied better in situ in bony specimens at the primary site of inflammation.